Niches in derivational morphology: Specialisation of suffixes within the formation of Portuguese deverbal nouns - Rodrigues, Alexandra Soares (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2020)
The aim of this paper is to study the specialisation of affixes following the same word- formation schema. The derivational morphology of Portuguese presents a multiplicity of suffixes that create deverbal nouns with the general meaning of ‘event’/‘result’/‘state’ (Rodrigues 2008). These suffixes may be exemplified by -ção (avaliação ‘evaluation’), -ment(o) (congelamento ‘freeze’), -dur(a) (cozedura ‘event of cooking’), -agem (aterragem ‘landing’), -nç(a) (cobrança ‘levy’), -ão (empurrão ‘push’), -nç(o) (falhanço ‘failure’), -id(o) (ladrido ‘barking’), -ic(e) (coscuvilhice‘gossip’), etc. Apparently, these suffixes are rivals, because they all generate the same kind of products from the same kind of bases. According to the Darwinian perspective presented by Lindsay & Aronoff (2013), Aronoff & Lindsay (2014, 2015) and Aronoff (2016), two affixes that are in mutual competition could either lead to the annihilation of one of them, or to their survival in the language, on the condition that they find a niche, i.e., a specialisation. In this paper, we will bring evidence to the specialisation of the suffixes -id(o), -ment(o) and -dur(a), among the suffixes that operate the construction of event /result /state deverbal nouns.